A theory on impact noise evaluation of a wood joist floor from equivalent circuit models and principle experiment - Iwashige, H.; Ohta, M. (Archives of Acoustics, 2001)
For the purpose of decreasing an impact sound level in the room below in a house, a new fundamental study on the impact sound of floors is given in the case of a wood joist floor above the structural concrete slab. In Japan, we have so many opportunities to use wood joist floors in housing. The wood joist floor is convenient and suitable for our Japanese life style. From such a practical viewpoint, a wood joist floor above the reinforced dense concrete floor is considered. Especially a new theoretical trial based on the introduction of equivalent concentrated constant circuit models of electric and mechanical types for an impact noise transmission of a wood joist floor is proposed first. Thus, a practical evaluation of the impact noise reduction can be theoretically estimated by the model method proposed. In the case of a wood joist floor using a resilient material under the wood joist, a quantitative improvement in the impact noise reduction has been systematically expected. Then, from an experimental viewpoint, we have succeeded in confirming the validity of our theory, especially in the case of the I.S.O. standard tapping machine. As a result, we have found a fairly good agreement between our theory and the principle experiment.